Substitution at boron in BODIPYs. Issue 53 (20th June 2022) - Gapare, Rosinah Liandrah; Thompson, Alison
Abstract : BODIPYs provide tunable electronic properties key to many applications. This article highlights structural modification at boron. Abstract : Recent synthetic achievements have led to 4, 4-disubstituted-4-bora-3a, 4a-diaza- s -indacenes (BODIPYs) with varying substituents at the meso, pyrrolic and/or boron sites, with each influencing photophysical properties and utility. This Feature article gives an overview of chemistry at the boron atom in BODIPYs, highlighting our contributions that evolved from synthetic curiosities and now offer this dipyrrolic skeleton potential across a wider range of applications. We first summarise preparative routes to BODIPYs through complexation of boron with the dipyrrinato ligand. The role of boron in protecting dipyrrins is then discussed, followed by strategies by which to achieve facile substitution at the boron atom.